If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -5x = 75 Solving 5 + -5x = 75 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -5x = 75 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = 75 + -5 -5x = 75 + -5 Combine like terms: 75 + -5 = 70 -5x = 70 Divide each side by '-5'. x = -14 Simplifying x = -14
| 2a^2-12=0 | | 0=39t-16t^2 | | 0=39-16t^2 | | 3(x-6.9)=8.7 | | 5n-21=-2+28 | | 0=5t+15-16t^2 | | (3x+5y)dx+(4x+6y)=0 | | x(x-3)=5 | | 10x^2+28x-48=0 | | 0=8t+24-16t^2 | | 4y^4-8y^3+6y=0 | | 0x+2y=8 | | f(x)=5x^3-4x^2-8x-25 | | (x-1)(x-1)=8 | | -7u-5=2u^2 | | 8.5x+5.33=67.77 | | 3g-49=17 | | (2x-20x)=0 | | -3x^2+36x-60=0 | | 2x^3-14x^2+14x+30=0 | | 0=12t-16t^2 | | 7n-2(n-3)=16 | | -w^2+w+20=0 | | -5w^2+14w-8=0 | | 5.2x=-28.08 | | 0=56-2x | | -4w^2+28w+72=0 | | -4w^2+28+72=0 | | (y^2+9y+20)(3y-24)=0 | | -3u^2+2u+21=0 | | 13x-5=0 | | -6y=3y |